Quality of water for drinking and other domestic purposes in some selected communities in Asutifi North District of Brong Ahafo Region, Ghana - Amoateng, Seth Kofi (KNUST, 2025)
The suitability of water for drinking and other domestic purposes from two major towns namely Ntotroso and Kenyasi in the Asutifi North District of Brong Ahafo Region were analyzed from November 2013 to February 2014.Water quality was monitored along four (4) main dimensions, namely metal concentration, physico-chemical, nutrient and microbiological parameters. Water samples were collected from twelve (12) sampling sites comprising two (2) major rivers, four (4) boreholes and six (6) hand dug wells and analyzed for temperature, pH, turbidity, conductivity, total dissolved solids, alkalinity, total hardness and some selected anions (phosphates, sulphates, chlorides, nitrates), some heavy metals (Cd, Pb, Zn, Hg, Cu, As, Fe) and microbiological indicators (faecal coliforms, total coliforms, Enterococci, E. coli). The concentration of lead for the water samples ranged from (0.08 mg/l to 0.33 mg/l). The largest (0.33 mg/l) concentration was recorded from the Goa River (located in Kenyasi) whilst the least (0.08 mg/l) was recorded in Borehole (located in Ahenebronum, Ntotroso). All the values recorded were above the WHO and Ghana Standards values of 0.010mg/l. The largest (3.12 mg/l) concentration of iron was recorded from hand dug well (located in Akataase, Ntotroso) whilst the least (0.83 mg/l) was recorded in Tano River (located at Ntotroso). All the iron concentrations were above the WHO limit (0.3mg/l) and Ghana Standard value (0.5mg/l). Mean alkalinity for the water samples ranged from (198.00 mg/l in borehole located in Ahenebronum, Ntotroso to 398.00 mg/l in hand dug well located in Akataase, Ntotroso). The only sample source found within the WHO acceptable limit (200 mg/l) was borehole located in Ahenebronum, Ntotroso. It was observed that the largest concentration of faecal coliforms was recorded in hand dug well located in Kwadaso, Kenyasi. No faecal coliforms were recorded in Boreholes located in Ampedwee Kenyasi, Adum Kenyasi and Akataase v Ntotroso. Water from these boreholes were therefore found to be within the acceptable WHO and Ghana Standards limits (0.0000 CFU/100ml).The largest concentration of E. coli was recorded in the Tano River. No E. coli was found in Borehole located in Ampedwee Kenyasi and Adum Kenyasi. Parameters such as mercury, arsenic, cadmium, zinc levels, turbidity, total dissolved solids, potassium and sodium were all within the acceptable limits of the World Health Organization (WHO) and Ghana Standards (GS) 175 – 1: 2008. Levels of lead, copper, iron, pH, conductivity, alkalinity, total hardness, calcium and manganese were above the acceptable guideline limits of the World Health Organization (WHO) and Ghana Standards (GS) 175 – 1: 2008. These make the water in the two communities (Kenyasi and Ntotroso) unsafe for drinking and other domestic uses without prior treatment or purification